1989
DOI: 10.1007/bf00384321
|View full text |Cite
|
Sign up to set email alerts
|

Trophic structure of a neotropical frugivore community: is there competition between birds and bats?

Abstract: Dietary overlap and competition between frugivorous birds and bats in the Neotropics have been presumed to be low, but comparative data have been lacking. We determined the diets of volant frugivores in an early successional patch of Costa Rican wet forest over a one month period. Ordination of the diet matrix by Reciprocal Averaging revealed that birds and bats tend to feed on different sets of fruits and that diets differed more among bat species than among bird species. However, there was overlap between Sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
61
1
8

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(74 citation statements)
references
References 43 publications
(45 reference statements)
4
61
1
8
Order By: Relevance
“…), resultando em uma disponibilidade "con stante" de frutos deste genero ao longo de todo 0 ano, 0 que poderia permitir tal especializa9ao como discutido para Carollia perspicillata em rela9ao a Piper. BONACCORSO (1979), PALMEIRIM et al (1989) RBIS et at. (1996) tam bern encontraram sementes de Solanum (alem de Ficus, Piper e Cecropia) nas fezes dos indivfduos capturados desta especie.…”
Section: Resultados E Discussaounclassified
See 1 more Smart Citation
“…), resultando em uma disponibilidade "con stante" de frutos deste genero ao longo de todo 0 ano, 0 que poderia permitir tal especializa9ao como discutido para Carollia perspicillata em rela9ao a Piper. BONACCORSO (1979), PALMEIRIM et al (1989) RBIS et at. (1996) tam bern encontraram sementes de Solanum (alem de Ficus, Piper e Cecropia) nas fezes dos indivfduos capturados desta especie.…”
Section: Resultados E Discussaounclassified
“…Na Costa Rica, tres especies de Carollia alimentam-se basicamente de Piper spp. (FLEMING 1985;PALMEIRIM et at. 1989).…”
Section: Fenologia E Caracterfsticas Das Especies De Frutosunclassified
“…Germination of Piper seeds varied between 53% and 89% of their seeds in this study ;Fleming (1988) and Palmeirim et al (1989) reported less germination from seeds defecated by Carollia bats. The reason for this difference is unknown.…”
Section: Discussionmentioning
confidence: 52%
“…For each seed sample, seeds from defecated, regurgitated and control treatments were placed in petri dishes (9 cm diameter) with moistened humid filter paper (Lieberman et al, 1979;Fleming et al, 1985;Palmeirim et al, 1989). Seeds weighing more than 2 g were placed in plastic pans (30 × 20 cm) with sterilized earth the day following its collection, with a similar number of seeds in treatments and controls.…”
Section: Seed Germination Experimentsmentioning
confidence: 99%
See 1 more Smart Citation